ПРОБЛЕМА МОРАЛЬНОГО ВЫБОРА В РАННИХ РАССКАЗАХ Д. СОЛЕВА (Филолошки студии, 2019)
The changes occurring in the Macedonian literature from the middle of the 1950-s to the middle of the 1960-s didn’t touch its artistical forms only, but they also touched the contents of works. The prose aspired to decide existential questions, including the question of a moral choice and responsibility connected to it. The last was of special interest for Dimitar Solev (born 1930), the outstanding prose writer, one of the key men in the literary life of that epoch. The first collection of his stories «Thawed snow» (1956) compelled attention of readers and critics right away, because of its aesthetic and ideological novelty. It was followed by the collection «Along the river and against the current» (1960) which developed the tendencies of «Thawed snow» fruitfully and showed the writer’s creative growth. The problem of the moral choice was developed on diverse material in Solev’s early stories. First of all, it was the actual military theme which was soil favorable to moral questions, but up to the middle of the 1950-s it was more considered from political positions. Solev is one of the writers who has looked the war newly and has represented it as «a moral examination». At the same time he shows convincingly, that the same moral questions arise at peace. Solev tries to avoid simplification; his stories terminate in a question addressed to the reader often. His purpose is to force the reader to reflect and to refuse the ideological schemes of thinking, imposed by the literature of the previous stage. Solev doesn’t achieve great creative success in realizing his intentions at once; but it’s obvious that his artistical language is perfected, his psychologism goes deeper, his treatment of moral problems becomes thiner, step by step.